Os significados político-institucionais do uso do veto na relação Executivo-Legislativo em Pelotas (RS) no período 2001-2008 - Hetsper, Rafael Vargas (2011)
This work has as its main purpose identifying the political-institutional meanings that the veto usage by the Mayor of Pelotas (RS) acquired for the relationship between the Executive and Legislative powers in a period of time between 2001 and 2008. As a secondary plan, it aims at finding behavioral changes in the relationship standard between the local powers when there was the change from Fernando Marroni s government (PT) (2001-04) to Bernardo de Souza (PPS)/Fetter Júnior s government (PP) (2005-08). Methodologically, it uses as its primary analysis object all the bills that, once approved by the City Council and then sent for executive deliberation in the period 2001-2008, could be vetoed by the City Mayor, and it elects as analytical variables factors related to the veto itself (type, motivation presented by the Executive power and appreciation result), as well as correlated to nature and the processing of bills (authorship, theme, urgent appreciation, incorporation of amendments to the initial project and processing time), and the influence of the Executive power on the legislative process (term of office of the Mayor and support of coalition government). The result of the multidimensional analysis of the 64 vetoes which occurred in the period (from a total of 950 identified bills) shows, in a coherent way, the present interpretations in the national Political Science, that the usage of veto by the Mayor of Pelotas in the period 2001-2008 meant the type of relationship developed between the local powers, which was of moderate conflict in the period 2001-2008, and of higher conflictive relation in the 2001-04 Government in comparison to the 2005-08 Government.